2012
DOI: 10.1186/1746-160x-8-25
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of osteoblast vitality influenced by the vitamins C and E

Abstract: Vitamin C and vitamin E are known as important cellular antioxidants and are involved in several other non-antioxidant processes. Generally vitamin C and vitamin E are not synthesized by humans and therefore have to be applied by nutrition. The absence or deficiency of the vitamins can lead to several dysfunctions and even diseases (e.g. scurvy). The main interest in this study is that vitamin C and E are known to influence bone formation, e.g. vitamin C plays the key role in the synthesis of collagen, the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
(36 reference statements)
2
40
0
3
Order By: Relevance
“…7C). The equilibrium modulus of the native cartilage tissue was preserved during 56 days of culture, similar to GAG con- 2002; Urban et al, 2012). In contrast to chondrocytes, bone cells require β-glycerophosphate, dexamethasone and serum, providing growth factors (Urban et al, 2012;Langenbach and Handschel, 2013).…”
Section: Study C: Defining Ex Vivo Critical Size Defectsmentioning
confidence: 79%
“…7C). The equilibrium modulus of the native cartilage tissue was preserved during 56 days of culture, similar to GAG con- 2002; Urban et al, 2012). In contrast to chondrocytes, bone cells require β-glycerophosphate, dexamethasone and serum, providing growth factors (Urban et al, 2012;Langenbach and Handschel, 2013).…”
Section: Study C: Defining Ex Vivo Critical Size Defectsmentioning
confidence: 79%
“…α -tocopherol is the most active and abundant form of Vitamin E. But it was found that when used individually it does not improve cell growth (14) which is why TRF was the choice of this study. It is worthy to mention that (15) addressed the issue of proliferation using a combination of α-tocopherols and selenium on gingival and periodontal fibroblasts using an in vitro model that mimics periodontal wound-healing process.…”
Section: Discussionmentioning
confidence: 99%
“…This could help these individuals in preventing the diseases by modifying their lifestyles like physical activities and nutritional intake. Osteoclastogenesis and osteoblastogenesis are some potential protective mechanisms of Vitamin C's role on bone health [29,30,31,32]. Previous cross-sectional studies have shown positive though inconsistent effects of Vitamin C on osteoporosis [33,34,35,36].…”
Section: Discussionmentioning
confidence: 99%